The Effects of Hospital Length of Stay on Readmissions for Children With Newly Diagnosed Acute Lymphoblastic Leukemia. Issue 5 (July 2016) - Wedekind, Mary F.; Dennis, Robyn; Sturm, Mollie; Koch, Terah; Stanek, Joseph; O'Brien, Sarah H.
Abstract : Although regimens for induction therapy in children with acute lymphoblastic leukemia (ALL) are similar across the United States, typical practice with regard to inpatient length of stay (LOS) varies by institution. US children's hospitals were categorized by typical induction LOS; and readmissions, pediatric intensive care unit (PICU) admissions, and average adjusted charges were compared for the first 30 days from initial admission. Using Pediatric Health Information System data, we extracted ALL induction admissions from 2007 to 2013. We categorized hospitals into 3 categories based on median LOS: short (⩽7 d), medium (8 to 15 d), or long (≥16 d). Median LOS varied from 5 to 31 days across hospitals. Thirty-day median inpatient costs per patient ranged from $32 K for short LOS, $40 K for medium LOS, and $47 K for long LOS. Compared with short LOS hospitals (n=14), medium LOS (n=8) and long LOS hospitals (n=8) had lower odds of PICU readmissions (odds ratio [OR], 0.68; P =0.0124 and OR, 0.31; P <0.001, respectively), and long LOS hospitals had lower odds of any readmission (OR, 0.44; P <0.0001). Average LOS for children with newly diagnosed ALL varies widely by institution. Children's hospitals that typically admit new ALL patients for >7 days have fewer PICU readmissions but substantial increase in total induction inpatient costs.